Interdisciplinary as a Process: Theoretical Considerations from the Humanities - Dorticós Torriente, Yanet; Abreus González, Adrian (Revista Universidad de Guayaquil, 2013)
The current article emphasises in the theoretical-methodological foundations about teaching with an interdisciplinary approach in the field of Humanities. It states that an interdisciplinary approach from the didactics of humanities, will allow to find the points of coincidence that typify the teaching of the subjects the humanities comprise, taking as starting point the analysis of the objectives and contents that are common to each subject. On the other hand, the article describes opinions related to the application of tasks with a systemic and interdisciplinary approach, since from the logic of conscious processes theory the system structure states that the object is always a process. In the particular case of this research, its materialization is present in the establishment of the interdisciplinary links in the disciplines the humanities include.